Body Image Perception and Weight Control Behavior among Secondary Level Students in Dharan - Rai, Salina; Sharma, Sharada (Asian Journal of Population Sciences, 2025)
Body image perception serves as a motivation for weight control practices in adolescents. This study evaluates secondary school students' body image perception and weight control behaviors. A descriptive cross-sectional study was conducted among 280 students enrolled in classes 9 to 11 in a secondary school. The sample was selected through multi-stage random sampling. To gather data, a self-administered questionnaire, Stunkard figure rating scale for perception of body image, and Weight control strategy scale were used to measure weight control behavior. Collected data was coded and entered into SPSS version 16, then analyzed using descriptive and inferential statistics, chi-square, and Mann-Whitney U test. The study found that 30.6% of students were satisfied with their body image, while 69.4% were dissatisfied. About 59.8% had normal weight, 23.6% were underweight, 13.3% were overweight, and 3.3% were obese. Moreover, 25% of students wanted to stay the same weight, 36.2% were trying to lose weight, and 29.2% were trying to gain weight. A significant association was found between body image perception, body mass index, and age. This study concluded that most students are dissatisfied with their body image and engage in weight control behaviors despite being of normal weight. Promoting satisfaction in body image perception and healthy weight management demands that programs related to healthy lifestyle choices be conducted in schools to educate them.